Teknik Pengajaran Bunyi Bahasa Arab - Abdul Hamid Hamid (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Phonetics is an important aspect of language learning—especially within the subject of listening competence. It is undoubtedly an urgent subject for all (foreign) languages learning including Arabic. As in the case of child in acquiring his/her mother language—strongly based on his/her competence of listening to the sounds—phonetic/phonological side of Arabic language must be presented since the early stages of its language learning. A conceptual analysis of phonetic/phonological side of Arabic language and its practical teaching, therefore, remain a must